Tillämpning av prissäkring i spannmålsodlingen - Näslund, Christian (2008)
The grain market is facing substantial changes. Tradionally, cereal has been a supply-led market i.e. supply conditions have had a major impact on price level or indirectly, through market interventions implemented through the Common Agriculture Policy (CAP). Just a few years ago, Sweden and the EU were not affected so strongly by world market prices for cereals. EU was a surplus-area and to a substantial degree a local market. Today, the situation is different. Both countries and industries are competing for the world's grain which means that a major production area with a good harvest face many buyers. In a situation where market forces play an increasingly important role, price movements have become a major problem. A market that is constantly exposed to sharp price changes makes specific demands on the farmer's decision-making process and increases the importance of having access to the tools that guard against unwanted price changes.